MENGENALKAN DUNIA INTERNASIONAL PADA GENERASI DINI (SEBAGAI KURIKULUM PEMBELAJARAN TK) - Arofah Minasari; Andrik Purwasito; Panji Binangun; Dyah Indraswati (Jurnal Warta Desa (JWD), 2021)
The international world is very closely related to children in the present era. One way to introduce it is by inserting international science in kindergarten level education. This knowledge is rarely conveyed to early age students because the lack of providing material training for kindergarten teachers and the diversity of educational backgrounds makes it difficult to determine international material. Community service uses the method of delivering basic international material to kindergarten teachers, then it can be delivered to kindergarten students. The learning activities that will be provided are in the form of: 1) selection of basic materials about the international world, 2) the use of effective and fun learning media for kindergarten students. This community service aims to increase the knowledge of kindergarten teachers and students about the international world through quality and fun learning activities.